The Role of Environmental Factors in the Development of Celiac Disease: What Is New? - Lionetti, Elena (Diseases, 2015)
Celiac disease (CD) is a systemic immune-mediated disorder caused by the ingestion of gluten-containing grains in genetically susceptible persons. It is one of the most common lifelong disorders, affecting approximately 1% of the general population. The prevalence of CD has increased in developed countries over recent decades, pointing to the role of additional environmental triggers other than gluten. It has been hypothesized that intestinal infections, the amount and quality of gluten, the intestinal microbiota, and early nutrition are all possible triggers of the switch from tolerance to an immune response to gluten. Two recent randomized controlled trials have been performed to clarify the relationship between the age at which gluten is introduced to a child’s diet and the risk of CD, showing that timing of gluten introduction does not modify the risk of CD. Both trials also showed that breastfeeding compared with no breastfeeding or breastfeeding duration or breastfeeding during gluten introduction have no effect on the risk of CD. The two trials, although not designed to address this issue, have shown that intestinal infections seem not to influence the risk of CD. Further studies are still needed to explore the missing environmental factors of CD for future prevention.